Genes of Inflammation and Placental Function GWAS Associated with Idiopathic Recurrent Miscarriage in the Kazakh Population - Alexandra Murtazaliyeva; Gulnara Svyatova; Galina Berezina; Gulfairuz Urazbayeva; Aigerim Sadyrbekova (Journal of Human Reproductive Sciences)
Background: The loss of two or more pregnancies is considered recurrent miscarriage (RM). One of the causes of this pathology is the occurrence of mutations both in pleiotropic and pathway-specific regulators and in structural genes. The simplest type of such mutations is single nucleotide polymorphisms. Aims: The aim of the study is to study the relationship between gene polymorphisms of anti- and pro-inflammatory cytokines – interferon-gamma (T874A), interleukin (IL1B) (C3954T), IL6 (G572C) and IL10 (G1082A); placental function, apoptosis and angiogenesis – apolipoprotein C-III (APOC3) (G5163C), kinase insert domain receptor (A1719T, G1192A), P53 (Arg72Pro) and signal transducer and activator of transcription 3 (STAT3) (C1697G) with the development of idiopathic RM (iRM) in the Kazakh population. Settings and Design: This was a case–control study. Materials and Methods: Molecular genetic studies were performed by TaqMan using a single site-specific amplification and real-time genotyping method in 302 women with iRM and 300 with normal reproduction. DNA isolation from the biomaterial was carried out using kits containing binding magnetic particles. Both samples were analysed for alleles and genotypes for the studied polymorphisms. Statistical Analysis Used: For statistical data processing, Pearson’s criterion, confidence interval (CI) and probability value were taken into account. Results: It was found that the carriage of unfavourable genotypes (G/C, C/C) for the G5163C polymorphism of the APOC3 gene increases the risk of developing iRM by three times (odds ratio = 3.0; 95% CI = 2.24–4.07). Other studied polymorphisms in the genes of ILs, interferon, P53 proapoptotic protein, kinase domain receptor and STAT3 transcription activator were not associated with RM. Conclusion: Significant associations of APOC3 gene genotypes with the development of iRM in the Kazakh population indicate the involvement of the placental system, which is realised by vascularisation defects and defective embryo implantation and leads to early pregnancy termination.